China’s Pearl River Delta Development: A game changer for Hong Kong - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
“Hong Kong government has to think out of the box and take initiative to lead Hong Kong to break the bottle neck in economy development,” said Dr. Fang Zhou, Research Director of One Country Two Systems Research Institute (OCTSRI), a non-government public policy think tank in Hong Kong, at a seminar organized by Lau Chor Tak Institute of Global Economics and Finance at the Chinese University of Hong Kong in November 2016.